Implementasi Sistem Full Day School dalam Meningkatkan Motivasi Belajar Mata Pelajaran Sejarah untuk Peserta Didik Kelas X di SMA Negeri 1 Ngunut - Fitania Syaharani Einadya Putri; Dita Hendriani (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This research is motivated by the implementation of the Full Day School system which has a significant impact on students' learning motivation. The formulation of the problem in this study is: (1) How is the implementation of the Full Day School system at SMA Negeri 1 Ngunut? (2) What is the strategy in increasing the motivation to learn history subjects for class X students at SMA Negeri 1 Ngunut? (3) What are the obstacles or barriers to the implementation of the Full Day School system in increasing the motivation to learn history subjects for class X students at SMA Negeri 1 Ngunut? The objectives of this research are (1) to find out the implementation of the Full Day School system at SMA Negeri 1 Ngunut, (2) to find out the strategies for increasing motivation to learn the subject of History for class X students at SMA Negeri 1 Ngunut, (3) to find out the obstacles or barriers to the implementation of the Full Day School system in increasing motivation to learn the subject of History for class X students at SMA Negeri 1 Ngunut. This study uses a qualitative-descriptive approach with data collection through observation, interviews, and documentation. Data analysis is carried out through the stages of data reduction, data presentation, and drawing conclusions. The informants of this study include History teachers and grade X students at SMA Negeri 1 Ngunut and all parties involved. The results of the study indicate that there are 2 strategies in increasing student learning motivation by History subject teachers at SMA Negeri 1 Ngunut, namely Intrinsic Motivation and Extrinsic Motivation. The obstacles or barriers experienced include: 1) Physical fatigue, 2) Mental saturation, 3) Teacher capacity and varied learning methods.